Alignment of electrospun polymer fibers using a concave collector. Issue 126 (10th December 2015) - Savva, Ioanna; Evaggelou, Eftychia; Papaparaskeva, Georgia; Leontiou, Theodoros; Stylianopoulos, Triantafyllos; Mpekris, Fotios; Stylianou, Kypros; Krasia-Christoforou, Theodora
Abstract : We present a simple concept for producing electrospun aligned polymer fibers based on the use of a static concave collector. Alignment quantification with a Fourier transform method showed an up to 70% fiber alignment in the collector's center area. Abstract : During recent years, electrospinning has become a powerful technique for the cost-effective production of fibrous materials with diameters ranging from a few nanometers up to a few micrometers. In a conventional electrospinning system the produced fibers are collected on a flat grounded collector in a random manner, resulting in isotropic non-woven fibrous mats. Many researchers have been focusing on the modification of the electrospinning collectors for inducing fiber orientation since aligned fibrous mats exhibit unique mechanical, electrical and optical properties rendering them highly attractive in many fields. Unlike other reported collector modification approaches developed for inducing fiber alignment via electrospinning, a very simple concept for producing aligned polymer fibers is presented herein, based on the modification of the electric field profile by replacing the flat metallic collector employed in a typical electrospinning set-up, with a concave one. The electric field profile developed in the case of the flat and the concave collectors was simulated performing a finite elements analysis. Most importantly electrospun meshes were produced and quantification of fiber alignment with a Fourier transform method on different deposition sites of the concave collector showed an up to 70% fiber alignment in the center area. This work creates new prospects towards the design of static collectors employed in electrospinning that could enable the fabrication of highly aligned electrospun fibers.